2021
DOI: 10.1371/journal.pone.0258701
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to infection prevention and control in Dutch residential care facilities for people with intellectual and developmental disabilities: A theory-informed qualitative study

Abstract: Background Care institutions are recognised to be a high-risk setting for the emergence and spread of infections and antimicrobial-resistant organisms, which stresses the importance of infection prevention and control (IPC). Accurate implementation is crucial for optimal IPC practice. Despite the wide promotion of IPC and research thereof in the hospital and nursing home setting, similar efforts are lacking in disability care settings. Therefore, this study aimed to assess perceived barriers and facilitators t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…The authors conducted 30 semi-structured interviews via phone call. Previous qualitative studies have shown that a sample size of 12 or more participants is necessary to reach data saturation (Fugard and Potts, 2015; Houben et al., 2021), whereas other qualitative research has demonstrated that sample size requirements for qualitative studies should be study-specific and focus on the quality and richness of the data (Vasileiou et al., 2018). Recruitment of participants in our study continued until saturation was achieved in sentiments among participants belonging to each treatment cohort.…”
Section: Methodsmentioning
confidence: 99%
“…The authors conducted 30 semi-structured interviews via phone call. Previous qualitative studies have shown that a sample size of 12 or more participants is necessary to reach data saturation (Fugard and Potts, 2015; Houben et al., 2021), whereas other qualitative research has demonstrated that sample size requirements for qualitative studies should be study-specific and focus on the quality and richness of the data (Vasileiou et al., 2018). Recruitment of participants in our study continued until saturation was achieved in sentiments among participants belonging to each treatment cohort.…”
Section: Methodsmentioning
confidence: 99%
“…While HCWs play a crucial role in preventing the spread of infectious diseases through individual behavioural changes [ 7 , 9 ], successful IPC requires considering broader multilevel factors [ 10 12 ]. These factors — operating at micro, meso, and macro levels — encompass barriers and facilitators that play an important role in shaping the success of IPC efforts [ 11 , 13 16 ]. At the micro level, client-related factors, such as a lack of patient education or non-compliance regarding IPC may come into play [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the micro level, client-related factors, such as a lack of patient education or non-compliance regarding IPC may come into play [ 16 ]. In addition, interpersonal factors, such as exemplary behaviour among colleagues and HCWs stimulating clients to implement adequate IPC practices can facilitate IPC [ 11 ]. At the meso level, facilities should have clear policies in place to guide IPC practices, such as continuous IPC training programmes [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that health and care workers in long-term care facilities are still lacking in core competencies for preventing and controlling emerging infectious diseases. Unfortunately, there are limited studies on infection prevention recommendations for health and care workers, such as the study of Houben et al (2021) on the barriers and facilitators of infection prevention and control in residential care facilities in the Netherlands.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, there are limited studies on infection prevention recommendations for health and care workers, such as the study of Houben et al. (2021) on the barriers and facilitators of infection prevention and control in residential care facilities in the Netherlands.…”
Section: Introductionmentioning
confidence: 99%